Gingival health condition and salivary physical properties among a group of patients with intermaxillary fixation in tow times intervals (Follow up study) - Entiqal N. Jasim Al-Wazni; Nadia A. Al- Rawi (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: One of the methods used in the treatment of maxillofacial fracture is intermaxillary fixation(IMF), the most common type is the Erich arch bar with interdental wiring. This study was conducted to investigate the impact of intermaxillary fixation on gingival health condition among a group of patients with facial fracture in relation to salivary physical properties. Materials and methods: Thirty patients with an age range of (17-37) years old with facial fractures and indicated for IMF. Plaque index and gingival index (Loe, 1967) were used to assess both of them before application and after removal of IMF. Unstimulated saliva sample collection was carried out under standardized conditions according to Navazesh and Kumer (2008) before IMF application and after removal to measure salivary flow rate and viscosity. Analysis of data was carried out using SPSS (version 18). Results: A higher mean values of plaque and gingival index were recorded after IMF removal than that before IMF application, with highly significant changes (p